2022
DOI: 10.3390/molecules27196327
|View full text |Cite
|
Sign up to set email alerts
|

Extracts Prepared from Feed Supplements Containing Wood Lignans Improve Intestinal Health by Strengthening Barrier Integrity and Reducing Inflammation

Abstract: Lignans are known to exhibit a broad spectrum of biological activities, indicating their potential as constituents of feed supplements. This study investigated two extracts derived from the feed supplements ‘ROI’ and ‘Protect’—which contain the wood lignans magnolol and honokiol (‘ROI’), or soluble tannins additional to the aforementioned lignans (‘Protect’)—and their impact on selected parameters of intestinal functionality. The antioxidant and anti-inflammatory properties of the extracts were determined by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Extract analyses were performed using reversed-phase chromatography, as described previously 16 using a Ultimate 3000 HPLC system comprised of a LPG-3400SD pump with built-in degasser, a WPS-3000 U(T)SL cooled autosampler, a temperature-controlled column compartment and an DAD-3000(RS) diode array detector equipped with the Chromeleon software (all Thermo Scientific, Dreieich, Germany). Analyte separation was performed on an Accucore C18 column (150 mm × 3.0 mm × 2.6 μm; Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Extract analyses were performed using reversed-phase chromatography, as described previously 16 using a Ultimate 3000 HPLC system comprised of a LPG-3400SD pump with built-in degasser, a WPS-3000 U(T)SL cooled autosampler, a temperature-controlled column compartment and an DAD-3000(RS) diode array detector equipped with the Chromeleon software (all Thermo Scientific, Dreieich, Germany). Analyte separation was performed on an Accucore C18 column (150 mm × 3.0 mm × 2.6 μm; Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Such assessments provide a better understanding of how plant extracts interact with cellular components, affect signaling cascades, and potentially influence gene expression associated with oxidative stress responses [ 21 ]. Two examples of cellular assays, which target different aspects of oxidative stress, include the ROS detection assay utilizing 2′,7′-dichlorodihydrofluorescein diacetate (H 2 DCF-DA) [ 12 , 22 , 23 ], and the Griess assay [ 24 ]. This ROS detection assay is based on the principle of detecting ROS-induced oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the safety of magnolol when taken orally has been confirmed, making it suitable for use as an additive in animal feed production ( Sarrica et al, 2018 ). Studies have revealed that dietary supplements magnolol can enhance intestinal health by promoting barrier integrity and exerting antioxidant and anti-inflammatory actions ( Heckmann et al, 2022 ). Broilers supplemented with magnolol have exhibited improved growth performance, higher quality meat, increased antioxidant capacity, and enhanced immune function ( Xie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%